James Joyce's "The Sisters": Implied Pederasty and Interpreting the Inexpressible. Issue 1 (1st June 2020) - Ryan, Barry
Abstract: The topic of pederasty in "The Sisters" has attracted extensive commentary. In this discussion, the boy's confusion, growing up at the crux of two views of masculinity, has not been explored. Moreover, Father Flynn's nostalgic view of boyhood, and his dependency on the company of the boy, also warrants exploration. Furthermore, little has been made of the boy's antagonistic relationship with Father Flynn's sisters, as there is evidence in the story that the boy is considered corruptive. It is my contention that pederasty is not the larger issue, as in another context, this could be contested. Rather, the boundary between the boy and adults is constructed across two opposing ideals of masculinity, obliterating any possibility of contestation. Subsequently, sentient and reflexive aspects of the boy's characterization deviate from how children are viewed by adult characters in Dubliners .